Simulation and Implementation of a High Performance Torque Control Scheme of IM Utilizing FPGA - R. Rajendran; N. Devarajan (International Journal of Electrical and Computer Engineering (IJECE), 2012)
Thi paper presents a novel approach to design and implementation of a high perfromane torque control scheme i.e. direct torque control with space vector modulation(DTC-SVM) of three phase induction motor using Field Programmable gate array (FPGA). The conventional direct torque control (DTC) is one of control scheme that is used commonly in induction motor control system. This method supports a very quick and precise torque response. However, the conventional DTC is not perfect and has some disadvantages. To minimize the ripples of the electromagnetic torque and flux linkage and to fix the variable switching frequency produced in the conventional DTC, this paper proposes improved DTC-SVM concept. Both simulation and experimental results show that the proposed scheme can dramatically improve the steady state performance while preserving the dynamic performance of the conventional DTC.DOI:http://dx.doi.org/10.11591/ijece.v2i3.208